Profile of Paediatric Traumatic Cataract and its Surgical Outcome - Panjiyar, Paras; Puri, Lila Raj (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Ocular injuries are the most common cause of acquired monocular blindness in children. Ocular trauma in children is mainly accidental and has an age-specific pattern. MATERIAL AND METHODS: This was a prospective study conducted at Sagarmatha Choudhary Eye Hospital, Lahan, Nepal. All children upto 15 years of age, who were diagnosed and managed for traumatic cataract between October 2012 and March 2014 (18 months period), were included in the study. Altogether 189 cases were enrolled for the study. RESULTS: Out of total 189 cases, 138(73%) were male, 51(27%) were female. 85% of the children were in the age group of 5 to 15 years while only less than 15% of the children were from the age group of 0 to 5 years. The most common cause of injury was wooden stick(34.4%) while 14.5% of the cases did not know the mode of trauma. CONCLUSION: Taking measures for prevention of ocular trauma among children is strategically important to reduce the stubborn prevalence of blindness in children.